2014
DOI: 10.1159/000358840
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on Changes in Regional Cerebral Blood Flow in Schizophrenia

Abstract: Aims: Although there have been no conclusive pathophysiological findings in support of the degeneration theory in the etiology of schizophrenia to date, results of our neuroimaging studies suggest functional changes in the brains of schizophrenics. We evaluated age-related changes of brain perfusion in medicated patients with schizophrenia. Method: In this study, we evaluated age-related changes in brain perfusion in medicated schizophrenia patients (n = 44) and control subjects (n = 37) undergoing 99m Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…In future studies it would be important to determine if aging and schizophrenia interact to further accelerate retinal microvasculature loss in older (>65) patients, as is the case for cerebral hypoperfusion. 58 A potentially important finding from this study is that the first episode and later episode schizophrenia groups did not differ on OCTA findings. This is in contrast to our earlier OCT study of retinal neural layer thickness in the same sample, 24 in which first episode patients' findings were within normal limits, whereas later episode patients demonstrated clear evidence of thinning at the macula.…”
Section: Dovepressmentioning
confidence: 58%
See 2 more Smart Citations
“…In future studies it would be important to determine if aging and schizophrenia interact to further accelerate retinal microvasculature loss in older (>65) patients, as is the case for cerebral hypoperfusion. 58 A potentially important finding from this study is that the first episode and later episode schizophrenia groups did not differ on OCTA findings. This is in contrast to our earlier OCT study of retinal neural layer thickness in the same sample, 24 in which first episode patients' findings were within normal limits, whereas later episode patients demonstrated clear evidence of thinning at the macula.…”
Section: Dovepressmentioning
confidence: 58%
“…Consistent with OCTA detecting changes in a range of neurological disorders, 11 it was recently shown that OCTA data predict brain vasculature changes in cerebral small vessel disease. 19 OCTA may therefore have utility as a screening tool for cerebral hypoperfusion, which is a risk factor for dementia, 68,69 but is also found in schizophrenia, 58 even at first episode. 70 Cerebral hypoperfusion is more common in older schizophrenia patients, however, where it worsens at a greater rate than expected from normal aging.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…The glutamate hypothesis is based on the finding that antagonists of the N-methyl-d-aspartate (NMDA) receptors induce schizophrenia-like symptoms in healthy individuals and exacerbate symptoms in patients with schizophrenia [40]. In addition, many reports have shown that schizophrenia indicates abnormalities of the blood flow in the brain [4144]. For example, Talati et al noted an increased hippocampal cerebral blood volume but a normal cerebral blood flow in patients with schizophrenia [41].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified significant bilateral temporal hypoperfusion related to aging and disease course. It has been suggested that this decrease in CBF with aging is paralleled with the degenerative changes observed in patients with schizophrenia (Schultz et al, 2002;Kawakami et al, 2014).…”
Section: Altered Cerebral Blood Flow In Schizophreniamentioning
confidence: 99%